THE STUDENTS’ RESPONSES TOWARD THE IMPLEMENTATION OF CROSSWORD PUZZLE IN TEACHING VOCABULARY TO THE SEVENTH GRADE STUDENTS IN ONE OF JUNIOR HIGH SCHOOL IN CIMAHI - Yeni Meliyani; Evie Kareviati (PROJECT (Professional Journal of English Education), 2021)
This research was intended to find out the students’ responses toward the implementation of crossword puzzle techniques in teaching vocabulary to the seventh-grade students at Junior High School. A descriptive qualitative method was used in this study. In collecting data the researcher used two instruments: classroom observation throughout the implementation of crossword puzzle in the classroom and from students’ interviews.  The researcher chose class VII B as respondents which consisted of 35 students. From the result, the researcher concluded that teaching-learning vocabulary by using crossword puzzle made the students’ easy to memorize the vocabulary and made the students’ more active in the class and the result also showed good responses from students, most of students felt interest and  like to learn vocabulary in a descriptive text by using crossword puzzle.